Wednesday

April 16, 2014

April 16, 2014

Posted by **Matt** on Tuesday, October 25, 2011 at 11:39pm.

(a) x1 + 5x2 − (2^0.5)x3 =1

(b) x1 + 3x2 + x1.x3 = 2

(c) x1 = −7x2 + 3x3

(d) x1^−2 + x2 + 8x3 =5

(e) x1^3/5 − 2x2 + x3 = 4

(f) πx1 − (2^0.5)x2 + 13x3 = 7^1/3

- Math -
**Jai**, Wednesday, October 26, 2011 at 2:14ama, c, f

**Related Questions**

Linear Alebra - Show that the transformation T:R^2->R^2 given T(x1,x2)=(3x1-...

Math - Show that the transformation T:R^2->R^2 given T(x1,x2)=(3x1-5x2,x1+2x2...

MATH - solve the system of linear equations using the Gauss- Jordan elimination ...

Calculus (Urgent!!) - Hello everyone, I need help with the following problems. ...

parabolas - how do i find the equaion of the following parabolas? 1)intercepts ...

algebra2 - solve the equation: First: x + 3y = 5 Second: 3x - y = 5 should i use...

college - Which of the following choices is a solution for: (-3-i)x1 + (1-2i)x2...

Linear Algebra - I previously posted this question under the wrong topic. Which ...

Math - Find the augmented matrix for each of the following systems of linear ...

math and desperate - What similarities and differences are there between ...